Clinico-radiological outcome of distal radius fractures managed with closed reduction during COVID-19 pandemic - Mahajan, Neetin; Mhatre, Jayesh; Talukder, Pritam (International Journal of Research in Orthopaedics, 2021)
Background: distal radius fractures are the most common fractures of the upper extremity and account for more than 1/6 of all fractures treated in emergency department the elderly population account for 18% of all distal end radius fractures and have a significant impact on health of young adults. An optimal outcome of closed treatment of a Colle’s fracture may depend on accurate reduction and adequate immobilization. Methods: A total 45 patients with displaced Colle’s-type fractures were subjected to treatment with closed reduction with manual manipulation. The fractures were assessed radiographically by measurement of the radial angle, dorsal tilt, and radial shortening before reduction, immediately after reduction, and at one and five weeks after reduction. Data was recorded and assessed. Results: Anatomical outcome as per Sarmiento criteria. 66.67% patients had excellent result with no residual Deformity, 17.77% patients had good result with mild residual deformity, 8.88% of them show fair results with moderate residual deformity and 6.66 % had poor outcome. Conclusions: Coronavirus disease 2019 (COVID-19) pandemic was burden on all including patients and medical fraternity, and considering looming threat of third wave and delta variant of virus, our study material can be used to make guidelines for optimal utilisation of orthopaedic fraternity, who have to work in COVID wards as well as trauma wards, our study shows that proper technique of fracture reduction with patient counselling and early physiotherapy can yield good results in fracture which can be managed conservatively.